Analisis Positioning Dan Brand Awareness Terhadap Keputusan Pembelian Handphone Blackberry Pada Mahasiswa Fakultas Ekonomi Ugm - Zuraida, Lukia; Novitasari, Dwi (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2014)
This research analyzed positioning and brand awareness on decision to purchase Blackberry handphone. The research done in 2013 using 100 students of economic faculties, UGM. The analytical method used was multiple regression. The results showed that a significant differences between positioning with purchasing decisions as indicated by the significance value below 0.005 and brand awareness with purchasing decisions have significance value below 0.000. This suggests that the higher positioning and brand awareness will be increased purchasing decisions.